Growth Performance of Lentil by the Effect of Irrigation and Boron Splitting Asfoliar Application (Bangladesh Agronomy Journal, 2020)
A field experiment was conducted for evaluating the effect of irrigation and boron splitting as foliar spray on growth and yield of lentil at the Research Field of the Department of Agronomy, Sher-e-Bangla Agricultural University, Dhaka from November, 2018 to March, 2019.Three levels of irrigation viz., I0: control, I1: one irrigation at 25 days after sowing (DAS), I2: two irrigations at 25 DAS and 40 DAS and boron was applied by four levels viz., B0: control, B1: 80% recommended dose as basal + rest 20% as foliar spray (FS) at pre-flowering (PF), B2: 60% RD as basal + rest 40% as FS at PF, B3: 40% RD as basal + rest 60% as FS at PF. The experiment was fully set up in a split-plot design with three replications. Two irrigations at 25 and 40 DAS result produced that the highest plant length, branches plant-1, leaves plant-1, dry weight plant-1. On the other hand, B3 (40% RD as basal + rest 60% as FS at PF) produced significantly the highest growth of lentil. Result also showed that the highest plant length (27.59 cm), number of branches (5.73) and plant dry matter (4.83 g) recorded from I2B3 combinations. Therefore, the combination of two irrigations at 25 and 40 DAS and boron at 40% RD as basal + rest 60% as foliar spray at pre-flowering might be considered as effective dose for the cultivation of lentil in Bangladesh.Bangladesh Agron. J. 2019, 22(2): 139-150